Stakeholder theory and actor‐network theory: The stakeholder engagement in energy transitions - Marcon Nora, Gabriela Almeida; Alberton, Anete; Ayala, Diego Hernando Florez (Business strategy and the environment, 2023)
The idea of sustainable development highlights the need to address economic, social, and environmental aspects to preserve the rights and needs of future generations. This paper proposes an association between stakeholder theory (ST) and Actor‐Network Theory (ANT) that can better explain the dynamics of actors in the energy sector, in the context of sociotechnical transitions to sustainability. By selectively examining the way in which different researchers perceive this subject, we intend to address how the engagement of the stakeholders can promote sociotechnical transitions in the energy sector trough the connection between ST and ANT. We aim to characterize the dynamics of stakeholder's engagement in sociotechnical transitions in the context of sustainability in the energy sector, trough the connection of the two theories. A narrative literature review was performed on scientific databases. The results showed that sociotechnical transitions in the energy sector require the involvement of multiple actors with different interests and that ST associated with ANT provides a good basis for research on this theme. The association of both theories highlights the importance of ST to enhance cooperation in the areas of clean energy research and technology, providing a theoretical tool for understanding the dynamics of transitions and its different pathways. For future studies, it is recommended to deepen the relationship between human and non‐human actors and their role as stakeholders.